PERLINDUNGAN HUKUM TERHADAP ANAK KORBAN CYBERBULLYING DI TINJAU DARI UNDANG- UNDANG NOMOR 11 TAHUN 2008 TENTANG INFORMASI DAN TRANSAKSI ELEKTRONIK - Rahmah, Siti; Darmiwati (Fakultas Hukum Universitas Islam Indragiri, 2024)
Bullying in the world (Cyberbullying) is an act that often occurs, but is often considered trivial even though the impact is very serious. This article examines legal protection for child victims of cyberbullying by outlining legal actions and remedies for child victims of cyberbullying. Cyberbullying is an act of violent crime committed against children as victims in physical, verbal and psychological forms. Cyberbullying is a new criminal phenomenon that must receive special attention from law enforcement. Cyberbullying is the treatment of terror and threats to the victim via online media, also known as the internet. In the case of bullying, usually a large number of people are involved and this behavior is carried out repeatedly to scare or embarrass the person being targeted, this is considered taboo. Generally, cyberbullying is carried out by certain people who want to find as much information as possible from child victims of slander, even threats. This law also explains that children as victims of criminal acts receive special protection where this special protection is provided by the government, regional government and other state institutions. The special protection given to this child includes rapid treatment and/or physical, psychological and social rehabilitation as well as prevention of disease and other health problems. Apart from that, children also have the right to receive psychosocial assistance during treatment until recovery and children also have the right to receive protection and assistance in every judicial process as explained in Law Number 35 of 2014 in conjunction with Law Number 23 of 2002 concerning Child Protection Article 20 which states The state, government, society, family and parents are obliged and responsible for children who are victims of bullying.